Studies in the Synthesis of 10 H-8-Bromo and 9-Methyl-1-Azaphenothiazine and Their 5-Oxide Derivatives via Smiles Rearrangement - Khatri Nee Taneja, Vineeta; Gupta nee Garg, Urmila; Sareen nee Grover, Vinita; Sharma, Kanti (Asian Journal of Chemistry, 2010)
The condensation of zinc salt of 2-amino-4-bromo/3-methyl benzene thiols and 2-chloro-3-nitropyridine yielded an amine and a sulfide. The sulfide was acetylated with acetic anhydride. The acetylated sulfide undergoes Smiles rearrangement in acetone and KOH (2.22 mole) to give the title compound. The amine also gave the same compound when treated with dimethyl sulfoxide and ethanolic potassium hydroxide. The acetylated sulfide rearranges to 10-acetyl derivative of the title compound when treated with one mole of potassium hydroxide in acetone. Further, 5-oxide derivatives can be obtained by reacting the title compound with hydrogen peroxide. The structures of all the compounds are confirmed by their IR and mass spectral data and elemental analysis.